A primer of magnetic stimulation as a tool for neuropsychology. - Walsh, V; Rushworth, M (1999)
Transcranial magnetic stimulation (TMS) offers the neuropsychologist a 'virtual lesion' method of investigating the effects of cortical dysfunction. Classical neuropsychology relies on patients with irreversible, and often diffuse brain lesions and these factors place limitations on the inferences that can be drawn about normal brain function. Thus the neuropsychologist is constrained by the extent to which the damaged brain undergoes reorganisation and by the inability to address questions regarding the timing of cognitive functions. TMS can disrupt cognitive functions for a few tens of milliseconds (although some effects of TMS can be seen for longer), with spatial resolution in the order of a centimetre and therefore allows one to study the role of brain areas without the masking effects of cortical reorganisation. The spatial and temporal resolutions are not unique to TMS but because TMS can be used as a temporary interference technique, it has a functional resolution with which one can address questions beyond the range of other neuroimaging and patient studies. Here we outline how TMS produces transitory 'lesion' effects, examine how the effects of stimulation spread in depth and breadth across the cortex and discuss the principles of the use of TMS in neuropsychology. Finally, we also itemise some issues of safety.